Dinamika Kapital Sosial dan Budaya Uma dalam Pembangunan Berkelanjutan di Pulau Siberut - Yudas Sabaggalet (Jurnal Antropologi: Isu-Isu Sosial Budaya, 2023)
The success of development is assessed based on economic indicators, some experts deemed that social and cultural capital have an important role in economic development. The failure of economic development in the Mentawai community does not pay attention to the dynamics of cultural and social capital. This study reveal how dynamics of cultural and social capital affect community development in uma. This research method uses a mix of quantitative and qualitative methods. The quantitative selection sample was taken by Slovin formula, while the qualitative informant was taken by purposive sampling. Data collection uses both survey, in-depth interviews and FGD. Data analysis uses the conceptual of social and cultural capital from Bourdiue. This article describes the comparison of the dynamics of social and cultural capital in the three regions that affect the life domains in uma. Uma forms both social and cultural capital related to the social organization and natural resource management domains. Uma formed social capital in the division of labour (sinuru') and the division of uma (rubeijat). Uma also formed cultural capital that menaged both agliculture (pumonean) with an integrated local knowledge farming system which is currently shift to market commodity and swamp cultivation (onaja) as local food domains such as sago, taro and bananas. The three regions show the low level of cooperation between the government and entrepreneurs in social and cultural capital in development programs. This study explain the importance of understanding the dynamics of social and cultural capital on the sustainability of development in uma domain.